Cyber-physical system based on image recognition to improve traffic flow: A case study - Vladimir Sanchez Padilla; Ronald A. Ponguillo; Arnaldo A. Abad; Lissette E. Salas (Institute of Advanced Engineering and Science, 2020)
Vehicular trafﬁc in metropolitan areas turns congested along either paths or periods. As a case study, we have considered a mass transport system with a bus ﬂeet that rides over exclusive lanes across streets and avenues in an urban area that does not allow the circulation of lightweight vehicles, cargo, and motorcycles. This trafﬁc ﬂow becomes congested due to the absence of restriction policies based on criteria. Moreover, the exclusive lanes are at ground level, decreasing lanes for other vehicles. The main objective of this proposal consists of controlling the access to the exclusive lanes by a cyber-physical system following authorization conditions, verifying the permission status of a vehicle by the accurate recognition of license plates to reduce trafﬁc congestion. Therefore, in the case of invading an exclusive lane without permission, the vehicle owner gets a notiﬁcation of the ﬁne with the respective evidence.